PENGARUH KEPEMILIKAN INSTITUSIONAL, RISIKO PERUSAHAAN DAN BEBAN IKLAN TERHADAP TAX AVOIDANCE - Nisa, Hana Khoirun; Sugeng, Andry (Publika Citra Media, 2024)
This study aims to determine and provide empirical evidence regarding the effect of institutional ownership, company risk and advertising expenses on tax avoidance. This research was conducted on primary consumer goods sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The data used in this study are secondary data. Sampling in this study was carried out using purposive sampling technique based on predetermined criteria, the research sample obtained the number of samples to be studied, which amounted to 17 companies with 5 years of observation, from the previous population of 113 companies. The panel data regression method is used as a research methodology in this study. Hypothesis testing was carried out using the 2th version of e-views. Based on the results of this study, it shows that simultaneously institutional ownership, company risk and advertising expense affect tax avoidance. then the results of this study also show that institutional ownership partially affects tax avoidance, company risk partially has no effect on tax avoidance and advertising expense partially has no effect on tax avoidance.